Extrahepatic portosystemic shunts as an unusual but treatable cause of hyperammonemic encephalopathy in a noncirrhotic patient – a case report. (May 2022) - Kühne Escolà, Jordi; Theysohn, Jens M.; Li, Yan; Forsting, Michael; Capetian, Philipp; Volkmann, Jens; Lange, Christian; Quesada, Carlos M.; Köhrmann, Martin; Frank, Benedikt; Kleinschnitz, Christoph
We report a case of hyperammonemic encephalopathy due to extrahepatic portosystemic shunts in a noncirrhotic patient. A 79-year-old woman suffered from episodic confusion, disorientation, dysphasia and fluctuating level of consciousness. Electroencephalography (EEG) showed encephalopathic changes and serum levels of ammonia were elevated. Further investigation revealed mesenterorenal and mesenterocaval shunts, which had possibly evolved after pancreatic surgery 5 years ago. After shunt obliteration, the symptoms completely resolved, ammonia levels dropped to the normal range and EEG findings normalized. Clinicians should be aware of this rare but treatable cause of encephalopathy in noncirrhotic patients.